Keragaman Identitas dalam Komunitas Konsumen: Pengamatan Partisipatif melalui Fashion Marketing - Ardianto, Eka (International Research Journal of Business Studies, 2008)
The rise of consumer communities leads the author to conduct this research. ‘Traditional’ approach views consumer community as a solid, stable, and homogeneous entity. However, using postmodernism approach, the author can spot identities in a consumer community. The exploration is done by participative observation through fashion marketing. It is found that there are four identities in the community, there are : 1) individual-culture identity (nature based), 2) collective-culture identity (future based), 3) temporary-structure identity (discussion based), and 4) permanent-structure identity (instruction based). Implication for marketer is also discussed at the end of this article.